Systematic Review of Psychological Well-Being among Working Mothers: Challenges, Protective Factors, and Recomendations - Pertiwi, Talitha Lintang (Universitas Negeri Semarang, 2025)
The psychological well-being of working mothers has become a significant issue in modern life, particularly due to increasing dual-role pressures between domestic and professional responsibilities. This condition can lead to stress, emotional exhaustion, and reduced quality of life if not balanced with adequate support. This study aims to identify the main challenges affecting the psychological well-being of working mothers, as well as protective factors that help them cope with such pressures. The method used is a systematic literature review of research articles published between 2016 and 2025. Literature was searched using the Publish or Perish application with the keywords: “psychological well-being” AND “working mom” OR “working mothers” AND “challenges” AND “protective factor”, yielding 600 articles. Inclusion criteria were articles in English or Indonesian, using quantitative or qualitative methods, involving working mothers as participants, and specifically addressing psychological well-being. Screening was conducted using Rayyan.ai, resulting in 14 eligible articles. The review followed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Findings show that dual-role burdens, blurred boundaries between work and home, and lack of social support are key stressors contributing to reduced well-being. Protective factors include family and coworker support, work flexibility, resilience, self-compassion, and the quality of mother-child relationships. The implications highlight the need for flexible work policies and cross-sectoral support systems. Future research is encouraged to explore different cultural contexts and to test interventions based on self-compassion, resilience, and supportive workplace policies for working mothers.